Structural Equation Model - Parsial Least Square Faktor-Faktor yang Memengaruhi Penjualan Coffee Shop Bacarito Kopi di Kota Padang - Devi Analia; Vilda Ayuni Sumardi; Ira Wahyuni Syarfi (Jurnal Ilmu Pertanian Indonesia, 2023)
This study aims to analyze the factors that affect sales of coffee shop Bacarito Kopi in Padang City. The research method used is a survey method. Consumers who are used as respondents are determined by accidental sampling with a total of 70 respondents. The data were obtained through interview guides and distributing questionnaires using a likert scale. The data analysis used is descriptive qualitative and quantitative analysis. Based on the research results, it is known that in carrying out sales activities, Bacarito Kopi has paid attention to controlled environmental factors, namely aspects of the marketing mix, consisting of price, promotion, place or distribution, and product quality. Other efforts made by Bacarito Kopi in conducting sales activities are improving the company’s performance by providing optimal service to the consumers, innovating to survive during intense competition, and expanding the market by opening business branches, and utilizing distribution intermediaries to expand the market. Based on the tests conducted on the research variables using the SEM-PLS analysis method with smartPLS software, it shows that the factors that have a significant effect on the sales of coffee shop Bacarito Kopi in Padang City are the seller’s ability (X1), competition (X2), product quality (X3), price (X4), and promotion (X5). Keywords: sales, marketing mix, coffee, bacarito kopi